Nonlinear firm dynamics - Davide Melcangi; Silvia Sarpietro (Federal Reserve Bank of New York, 2024)
This paper presents empirical evidence on the nature of idiosyncratic shocks to firms and discusses its role for firm behavior and aggregate fluctuations. We document that firm-level sales and productivity are hit by heavy-tailed shocks and follow a nonlinear stochastic process, thus departing from the canonical linear. We estimate a state-of-the-art model to flexibly capture the rich dynamics uncovered in the data and characterize the drivers of nonlinear persistence and non-Gaussian shocks. We show that these features are crucial to get empirically plausible volatility and persistence of micro-originated (granular) aggregate fluctuations.
Keywords: D22; E23; E32; 330; firm dynamics; productivity; nonlinearities; non-Gaussian shocks; granular fluctuations